Necropolitics revisited: how mainstream media coverage of Marielle's shooting in Brazil depoliticises her struggle and reinforces neoliberal logics (Alternautas, 2022)
Until her assassination on the 14th of March 2018, activist Marielle Franco was a voice of her comunidade, the favela of Maré in Rio de Janeiro, and repeatedly denounced police brutality and the genocide of Black people, a topic that is not often covered by mainstream media in Brazil. When Marielle was murdered, pressure by national and international press prompted the ex-president Michel Temer to affirm that the case would be investigated and solved in 48 hours. Many months later, the crime has not yet been solved, although Rio police have identified a group of suspects who are part of a very dangerous militia in the state of Rio de Janeiro, with at least one tie to Jair Bolsonaro’s family. The following turbulent months of 2018 made journalists follow other news: the imprisonment of former president Luiz Inácio Lula da Silva, the continuation of Lava Jato’s corruption investigation, and the violence and polarization associated with Brazil’s presidential elections. The stories about Marielle quickly faded away. When the crime happened, however, there was a considerate amount of coverage by mainstream media. That is the subject of this article.